Tablet and web-based audiometry to screen for hearing loss in adults with cystic fibrosis. Issue 8 (14th May 2020) - Vijayasingam, Anitha; Frost, Emily; Wilkins, Julie; Gillen, Lise; Premachandra, Presanna; Mclaren, Kate; Gilmartin, Desmond; Picinali, Lorenzo; Vidal-Diez, Alberto; Borsci, Simone; Ni, Melody Zhifang; Tang, Wai Y; et al.
Abstract : Introduction: Individuals with chronic lung disease (eg, cystic fibrosis (CF)) often receive antimicrobial therapy including aminoglycosides resulting in ototoxicity. Extended high-frequency audiometry has increased sensitivity for ototoxicity detection, but diagnostic audiometry in a sound-booth is costly, time-consuming and requires a trained audiologist. This cross-sectional study analysed tablet-based audiometry (Shoebox MD) performed by non-audiologists in an outpatient setting, alongside home web-based audiometry (3D Tune-In) to screen for hearing loss in adults with CF. Methods: Hearing was analysed in 126 CF adults using validated questionnaires, a web self-hearing test (0.5 to 4 kHz), tablet (0.25 to 12 kHz) and sound-booth audiometry (0.25 to 12 kHz). A threshold of ≥25 dB hearing loss at ≥1 audiometric frequency was considered abnormal. Demographics and mitochondrial DNA sequencing were used to analyse risk factors, and accuracy and usability of hearing tests determined. Results: Prevalence of hearing loss within any frequency band tested was 48%. Multivariate analysis showed age (OR 1.127; (95% CI: 1.07 to 1.18; p value<0.0001) per year older) and total intravenous antibiotic days over 10 years (OR 1.006; (95% CI: 1.002 to 1.010; p value=0.004) per further intravenous day) were significantly associated with increased risk of hearing loss. Tablet audiometry had good usability, was 93% sensitive, 88% specific with 94% negative predictive value to screen for hearing loss compared with web self-test audiometry and questionnaires which had poor sensitivity (17% and 13%, respectively). Intraclass correlation (ICC) of tablet versus sound-booth audiometry showed high correlation (ICC >0.9) at all frequencies ≥4 kHz. Conclusions: Adults with CF have a high prevalence of drug-related hearing loss and tablet-based audiometry can be a practical, accurate screening tool within integrated ototoxicity monitoring programmes for early detection.